Guar Gum as Corrosion Inhibitor for Carbon Steel in Sulfuric Acid Solutions - Abdallah,M. (2004)
Guar gum was tested as corrosion inhibitor for carbon steel in 1 M H2SO4 solution using weight loss and Tafel polarization techniques. The results showed that the inhibition efficiency increases with the increasing of the guar gum concentration, which act as an inhibitor of the mixed type. The inhibition action of guar gum was discussed in terms of its horizontal adsorption on the metal surface. The adsorption follows Langmuir adsorption isotherm. The effect of the presence of chloride ion in pitting corrosion was analyzed by the potentiodynamic anodic polarization technique. The pitting corrosion potential changes with the concentration of Cl- ion according to a sigmoid S-shaped curve. This behaviour was explained on the basis of the formation of passivatable, active and continuously propagated pits.